Systematic Desensitization Techniques to Reduce Anxiety of Facing Examinations in Middle School Students - Sulistiyoningrum, Renny; Mulawarman, Mulawarman (Universitas Ahmad Dahlan, 2019)
The study aims to determine the effectiveness of systematic desensitization techniques to reduce exam anxiety in grade VIII students at SMP N 3 Ungaran. The study used a quantitative approach with experimental types and the One Group Pretest-Posttest Design. The subjects in this study were five students.Â This study uses a random assignment to determine the subject of the study. Data collection using a scale of anxiety to face the test. The study results were analyzed using the Wilcoxon Signed Ranks Test. The results of the analysis show that Rational Emotive Behavior (REB) counseling with systematic desensitization techniques is effective in reducing student anxiety in facing exams. The results of the study provide recommendations for counselors to facilitate students in reducing anxiety in facing exams in students through systematic sensitization techniques. Further research can use the results of the study as a reference to determine the effectiveness of other techniques in counseling to reduce exam anxiety.